Environmental, social, and governance perspectives on economic development in Asia - Barnett, William A.,; Sergi, Bruno S., (International symposia in economic theory and econometrics ;, 2021)
This volume of the International Symposia in Economic Theory and Econometrics explores the latest economic and financial developments in Asia. Chapters cover a range of topics such as the consequences of green supply chain integration and environmental uncertainty on performance, along with the effects of perceived organisational support, transformational leadership, and teamwork on employee engagement. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as corporate social responsibility and the effects of public policy. Environmental, Social, and Governance Perspectives on Economic Development in Asia also includes empirical studies in financial economics and public governance. For example, one chapter analyses the impact of COVID-19 pandemic risk and lockdown on the Indian economy, while another empirically studies the influence of word of mouth variables on visits and re-visits for ecotourism in West Java. Together, ISETE 29 volume B, is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.